FOMO on New Year’s Eve: The Role of Social Media in Transforming How MSMEs Interact with Consumers - Jayanto, Imam; Anggraeni, Inda Permata; Alfakih, Ahmad Fauzi (ADMAN: Journal of Contemporary Administration and Management, 2025)
The phenomenon of Fear of Missing Out (FOMO) has become an important factor influencing consumer behavior, particularly during special moments such as New Year’s Eve. This study aims to analyze the role of social media in transforming how Micro, Small, and Medium Enterprises (MSMEs) interact with consumers through the perspective of FOMO. The research adopts a qualitative approach using a literature review method, in which data were obtained from scientific articles and credible online sources published between 2013 and 2025. From an initial pool of 50 articles, a rigorous selection process resulted in 25 articles being used as the basis for analysis. The findings indicate that social media functions as a strategic medium that enables MSMEs to leverage FOMO to increase engagement, sales, and brand awareness. A case study from the bakery industry in the United Kingdom demonstrates that campaigns based on exclusive and time-sensitive content are able to stimulate rapid consumer responses and expand digital interactions. This study highlights the importance of content creativity, an understanding of digital audiences, and precise timing to ethically maximize the effects of FOMO. The implications of this research include the development of digital marketing strategies for MSMEs and theoretical contributions to consumer behavior studies in the era of social media.